2017
DOI: 10.1002/ajh.24946
|View full text |Cite
|
Sign up to set email alerts
|

MECOM, HBS1L‐MYB, THRB‐RARB, JAK2, and TERT polymorphisms defining the genetic predisposition to myeloproliferative neoplasms: A study on 939 patients

Abstract: Polycythemia vera (PV), essential thrombocythemia (ET) and primary myelofibrosis (PMF) are classical myeloproliferative neoplasms (MPN), characterized by specific somatic mutations in JAK2, CALR or MPL genes. JAK2 46/1 and TERT rs2736100 polymorphisms are known to significantly predispose to MPN. This study aimed to establish the additional contribution of the recently described MECOM rs2201862, HBS1L-MYB rs9376092 and THRB-RARB rs4858647 polymorphisms to the occurrence of MPN. These three polymorphisms, along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 20 publications
(31 reference statements)
4
32
0
Order By: Relevance
“…Previous studies had suggested that patients with type 2/like CALR mutations were phenotypically more aligned with JAK2 ‐mutated cases . Consistent with this conjecture, in one large study of 939 patients with MPN, the JAK2 46/1 MPN predisposition allele was significantly associated with JAK2 and type 2/like CALR and not with type 1/like CALR mutations . One notable exception is the risk of thrombosis, which is a characteristic feature of JAK2 and possibly MPL mutations, and not necessarily dependent on the presence or absence CALR mutations …”
Section: Discussionmentioning
confidence: 55%
“…Previous studies had suggested that patients with type 2/like CALR mutations were phenotypically more aligned with JAK2 ‐mutated cases . Consistent with this conjecture, in one large study of 939 patients with MPN, the JAK2 46/1 MPN predisposition allele was significantly associated with JAK2 and type 2/like CALR and not with type 1/like CALR mutations . One notable exception is the risk of thrombosis, which is a characteristic feature of JAK2 and possibly MPL mutations, and not necessarily dependent on the presence or absence CALR mutations …”
Section: Discussionmentioning
confidence: 55%
“…However, in 2010, calreticulin ( CALR ) gene mutations had not yet been identified, therefore the mutational status of V617F negative TE and MF patients could not be correctly assessed. After the identification of CALR mutations, further studies produced conflicting results regarding the frequency of the haplotype GGCC_46/1 in this group of MPN patients, mostly suggesting a lack of association [ 14 , 21 , 22 , 23 ]. Therefore, the possible association between the occurrence of the haplotype GGCC_46/1 and JAK2 V617F negative MPN cases warrants further investigation.…”
Section: Frequency Of the Haplotype Ggcc_46/1 Imentioning
confidence: 99%
“…These findings suggest that that the JAK2 haplotype GGCC_46/1 does not explain familial MPNs, which account for 5–10% of all MPN cases [ 28 , 29 , 30 , 31 ]. At the same time, it was found that the rs2736100 SNP, located in the second intron of the telomerase reverse transcriptase ( TERT ) gene, had a different allele frequency in familial MPN compared to sporadic cases [ 27 ] and exhibited a strong cancer predisposition effect in all MPN subtypes, regardless of the JAK2 gene mutations occurrence [ 23 , 32 ]. The TERT gene at 5p15.33 encodes the catalytic subunit of the telomerase complex, playing an important role in maintaining telomere length [ 33 ].…”
Section: The Role Of the Jak2 Haplotype mentioning
confidence: 99%
See 2 more Smart Citations